Phylogenetic and Pathotypic Characterization of Newcastle Disease Viruses Circulating in South China and Transmission in Different Birds - Kang, Yinfeng; Xiang, Bin; Yuan, Runyu; Zhao, Xiaqiong; Feng, Minsha; Gao, Pei; Li, Yanling; Li, Yulian; Ning, Zhangyong; Ren, Tao (Frontiers in Microbiology, 2016)
Although Newcastle disease virus (NDV) with high pathogenicity has frequently been isolated in poultry in China since 1948, the mode of its transmission among avian species remains largely unknown. Given that various wild bird species have been implicated as sources of transmission, in this study we genotypically and pathotypically characterized 23 NDV isolates collected from chickens, ducks, and pigeons in live bird markets (LBMs) in South China as part of an H7N9 surveillance program during December 2013–February 2014. To simulate the natural transmission of different kinds of animals in LBMs, we selected three representative NDVs—namely, GM, YF18, and GZ289—isolated from different birds to evaluate the pathogenicity and transmission of the indicated viruses in chickens, ducks, and pigeons. Furthermore, to investigate the replication and shedding of NDV in poultry, we inoculated the chickens, ducks, and pigeons with 106 EID50 of each virus via intraocular and intranasal routes. Eight h after infection, the naïve contact groups were housed with those inoculated with each of the viruses as a means to monitor contact transmission. Our results indicated that genetically diverse viruses circulate in LBMs in South China’s Guangdong Province and that NDV from different birds have different tissue tropisms and host ranges when transmitted in different birds. We therefore propose the continuous epidemiological surveillance of LBMs to support the prevention of the spread of these viruses in different birds, especially chickens, and highlight the need for studies of the virus–host relationship.